Towards Volumetric Video Conferencing - Cesar, Pablo (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia), 2023)
With Social Extended Reality (XR) emerging as a new medium, where users can remotely experience immersive content with others, the vision of a true feeling of ‘being there together’ has become a realistic goal. This keynote will provide an overview about the challenges to achieve such a goal, based on results from practical case studies like the TRANSMIXR and MediaScape XR projects. We will discuss about different technologies, like point clouds, that can be used as the format for representing highly-realistic digital humans, and about metrics and protocols for quantifying the quality of experience. The final intention of the talk is to shed some light on social XR, as a new group of virtual reality experiences based on social photorealistic immersive content. We will discuss about the challenges regarding production and user-centric processes, and discover the new opportunities open by this new medium